(untitled) (AYUSHDHARA, 2020)
Menopause is normal physiological change and an important transition in women’s life. Onset of menopause has important implication on women’s fertility and health. Natural menopause is an age-related decrease in endocrine function of ovaries. Natural menopause occurs at or after age 45-55 years. Menstruation either stops suddenly or becomes irregular or less in quantity. During menopause physical, physiological and psychological changes occur. Few studies on menopausal syndrome and yoga have been carried out throughout the globe. The study was conducted in 30 clinically diagnosed patients of Menopausal syndrome and its management with Bhramari Pranayam. It was observed that the patients of Menopausal syndrome are showed highly significant improvements in psychological symptoms. No adverse effects were noted in any of the patients during the trial period. Such an approach of giving yoga therapies can help improve quality of life for patients suffering from various illnesses and thus provide a big respite from mental illnesses and life stressors that disrupt the society at large in today’s day and time.